CFRP Strengthening and Rehabilitation of Inner Corroded Steel Pipelines under External Pressure - Jianxing Yu; Weipeng Xu; Yang Yu; Fei Fu; Huakun Wang; Shengbo Xu; Shibo Wu (Journal of Marine Science and Engineering, 2022)
The objective of this study was to investigate the performance of pipelines repaired with carbon-fibre-reinforced polymer (CFRP) under external pressure. The repaired pipeline experienced defects in terms of thinning of its local inner wall. The three-dimensional finite element method was used to analyse the collapse pressure of repaired pipes with internal corrosion defects. The traction–separation law and interlaminar damage criterion were applied to simulate the collapse process of repaired pipes. The results show that the collapse pressure of the composite-repaired pipe increased and the CFRP significantly reduced the strain in the defect region. It was observed that the ovality of the corrosion defect region was reduced and that the repair effectiveness mainly depended on the length, thickness, and interlayer cohesion.